Pipeline Power: A Case Study of Strategic Network Investments - Onur Cobanli; Franz Hubert (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We use the Shapley value and the nucleolus to analyze the impact of three controversial pipeline projects on the power structure in the Eurasian trade of natural gas. Two pipelines, `Nord Stream' and `South Stream', allow Russian gas to bypass transit countries, Ukraine and Belarus. The third project, `Nabucco', aims at diversifying Europe's gas imports by accessing producers in Middle East and Central Asia. For the Shapley Value we obtain a clear ranking of the projects which corresponds to the observed investment patterns. Nord Stream's strategic value is huge, easily justifying the high investment cost for Germany and Russia. The additional leverage obtained through South Stream is much smaller and Nabucco is not viable. For the nucleolus in contrast, none of the pipelines has any strategic relevance at all, which appears to be at odds with the empirical evidence.
Keywords: C71; L50; L95; 330